2011
DOI: 10.5152/jtgga.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide levels and endothelial nitric oxide synthase gene polymorphisms in Turkish women with idiopathic recurrent miscarriage

Abstract: Objective: To determine whether endothelial nitric oxide synthase (eNOS) gene polymorphisms are associated with an increased risk for Idiopathic Recurrent Miscarriage (IRM) in the Turkish population and to evaluate the association between Nitric Oxide (NO) levels and eNOS gene polymorphisms in women with IRM. Material and Methods:A total of 120 Turkish women were enrolled in this study in four groups. Of these, 30 women were first trimester pregnant who had IRM (Group I). Thirty healthy multipara women were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Studies reported that VEGF (vascular endothelial growth factor) ‐related genes might be associated with pregnancy loss as lower VEGF expression in early pregnancy has been associated with spontaneous abortions 76–78 . However, no association between −2578C/A, −634G/C, and 936C/T polymorphisms in VEGF , 79,80 rs2070744, and rs61722009 variants in NOS gene 81 have been reported. The TP53 (another gene related to angiogenesis and fetal development), also known as tumor suppressor gene, plays a key role in regulating apoptosis, cell cycle, and DNA damage 82,83 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported that VEGF (vascular endothelial growth factor) ‐related genes might be associated with pregnancy loss as lower VEGF expression in early pregnancy has been associated with spontaneous abortions 76–78 . However, no association between −2578C/A, −634G/C, and 936C/T polymorphisms in VEGF , 79,80 rs2070744, and rs61722009 variants in NOS gene 81 have been reported. The TP53 (another gene related to angiogenesis and fetal development), also known as tumor suppressor gene, plays a key role in regulating apoptosis, cell cycle, and DNA damage 82,83 .…”
Section: Resultsmentioning
confidence: 99%
“…75,76 Studies reported that VEGF (vascular endothelial growth factor) -related genes might be associated with pregnancy loss as lower VEGF expression in early pregnancy has been associated with spontaneous abortions. [76][77][78] However, no association between −2578C/A, −634G/C, and 936C/T polymorphisms in VEGF, 79,80…”
Section: Angiogenesis and Vascularization-related Polymorphisms And Irplmentioning
confidence: 97%
“…But the results are inconsistent. [9,10] This may be due to racial and regional differences as well as the fact that the sample size is too small to objectively reflect the relevance between eNOS gene polymorphism and URSA. In order to compare different research results more scientifically and objectively.…”
Section: Introductionmentioning
confidence: 99%